Pengujian Karakter Kuantitatif dan Kualitatif Bayam Varietas Bikaler 2: Quantitative and Qualitative Characters of Bikaler 2 Variety of Spinach - Heri Kustanto; Renan Subantoro; Hilmi Arija Fachriyan; Endah Subekti; Lu’lu’a Ulyn Ni'mah (Mediagro: Jurnal Ilmu-ilmu Pertanian, 2026)
Spinach also contains several vitamins, such as vitamins A, B, and C. Spinach has a soft texture. Its fiber content is quite high, which can help smooth the digestive process. Spinach also contains mineral salts such as calcium, phosphorus, and iron, which are necessary for humans. This study aims to determine the qualitative and quantitative characteristics of the Bikaler 2 spinach variety compared to cek, a commercial variety that is widely favored and grown by the community. The research results indicate that quantitatively, the Bikaler 2 variety has high productivity, a large stem diameter, and high leaf length and width. The qualitative characteristics of Bikaler 2 spinach differ from existing varieties, particularly its two leaf colors, green and purple, making it more attractive to consumers. Keywords: Spinach, productivity, vegetative, harvest.